Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1097/00004647-200205000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Factor Erythropoietin Fosters Neuroprotection through Novel Signal Transduction Cascades

Abstract: Summary:In addition to promoting the survival, proliferation, and differentiation of immature erythroid cells, erythropoietin and the erythropoietin receptor have recently been shown to modulate cellular signal transduction pathways that extend beyond the erythropoietic function of erythropoietin. In particular, erythropoietin has been linked to the prevention of programmed cell death in neuronal systems. Although this work is intriguing, the underlying molecular mechanisms that serve to mediate neuroprotectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
0
8

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(158 citation statements)
references
References 125 publications
(139 reference statements)
5
143
0
8
Order By: Relevance
“…Recent studies have shown that in addition to promoting the survival, proliferation and differentiation of immature erythroid cells through associations with the ERK pathway, Epo has been shown to modulate other MAPK and cellular signal transduction pathways (JNK and p38) (Silva et al, 1999;Kapur and Zhang, 2001;Chong et al, 2002). Indeed, it has been suggested that the ERK MAPK pathway may not be the principal mechanism of Epo activity (Kolonics et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that in addition to promoting the survival, proliferation and differentiation of immature erythroid cells through associations with the ERK pathway, Epo has been shown to modulate other MAPK and cellular signal transduction pathways (JNK and p38) (Silva et al, 1999;Kapur and Zhang, 2001;Chong et al, 2002). Indeed, it has been suggested that the ERK MAPK pathway may not be the principal mechanism of Epo activity (Kolonics et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…60 The antiapoptotic action of NF-kB in neurons also involves activation of Akt1 and Bad phosphorylation 41,61 as well as Bcl-xL upregulation. 62,63 Bcl-xL was also found induced by EPO in a study where DNA microarrays were used to identify modulated genes in PC12 neuronal-like cells 64 and in vivo in a gerbil model of cerebral ischemia. 62 Of note, Ruscher et al, 61 studying the protective effect of EPO against oxygen glucose deprivation-induced apoptosis of primary cortical neurons, confirmed that the protective effect requires Jak2, as shown by Digicaylioglu and Lipton, 60 and of PI(3)Kinase, as shown by us, 39 using specific inhibitors of these kinases.…”
Section: Epo Signaling In Nervous System Cellsmentioning
confidence: 91%
“…2,4 Anemic stress, insulin release, and several cytokines, including insulinlike growth factor (IGF), tumor necrosis factor α (TNF-α), interleukin 1β (IL-1β), and interleukin 6 (IL-6), also can lead to increased expression of EPO and the EPOR. [2][3][4] Several recent studies have outlined the mechanisms by which EPO may prevent cell injury (Figure). Protection by EPO in a number of cellular systems is robust and EPO prevents apoptosis from a number of sources, including reduced or absent oxygen tension, excitotoxicity, and free radical exposure.…”
Section: Structure Expression and Cellular Pathways Of Epomentioning
confidence: 99%